2014
DOI: 10.1007/s13105-013-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of hydro-alcoholic extract of Caralluma fimbriata against high-fat diet-induced insulin resistance and oxidative stress in Wistar male rats

Abstract: The main aim of this study was to investigate the beneficial effects of hydro-alcoholic extract of Caralluma fimbriata (CFE) on the effects of high-fat diet feeding on insulin resistance and oxidative stress in Wistar rats. High-fat diet (60% of fat) and CFE (200 mg/kg body weight/day) were given concurrently to the rats for a period of 90 days. Feeding with high-fat diet resulted in the development of hyperglycemia, hyperinsulinemia, hyperleptinemia, and hypertriglyceridemia and impaired insulin sensitivity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 52 publications
3
18
0
1
Order By: Relevance
“…Several studies had revealed that high fat diet could cause hepatic steatosis, hyperlipidemia, hyperinsulinemia, obesity, insulin resistance and other lipid metabolism disorder disease in humans and in laboratory animals [ 1 , 2 ]. The results of the present study showed that high-fat diet led to significant increase in body weight, hyperlipidemia, hyperglycemia, hyperinsulinemia, and hepatic lipid accumulation, which were in agreement with previous studies [ 1 , 2 , 23 ]. Phenolic compounds, which are widespread in plants, showed therapeutic effects to obesity and other HFD-induced disease [ 1 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Several studies had revealed that high fat diet could cause hepatic steatosis, hyperlipidemia, hyperinsulinemia, obesity, insulin resistance and other lipid metabolism disorder disease in humans and in laboratory animals [ 1 , 2 ]. The results of the present study showed that high-fat diet led to significant increase in body weight, hyperlipidemia, hyperglycemia, hyperinsulinemia, and hepatic lipid accumulation, which were in agreement with previous studies [ 1 , 2 , 23 ]. Phenolic compounds, which are widespread in plants, showed therapeutic effects to obesity and other HFD-induced disease [ 1 , 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…As previously expressed, insulin resistance is another key pathophysiological feature and pathogenesis in high fat diet mice [ 2 , 20 , 21 ]. The hyperlipidemia and hyperglycemia induced by high fat diet could decrease the number of insulin receptors, glucose transport and metabolism thereby increasing insulin resistance and reducing insulin sensitivity [ 23 ]. Insulin signaling is a cascade of events initiated by the activation of insulin receptor substrates (IRS).…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al [55] reported the potential of C. attenuate in the treatment of diabetes. Similarly, C. fimbriata may be beneficial for the suppression of high-fat dietinduced insulin resistance and oxidative stress [56].…”
Section: Non-enzymatic Antioxidant Contentsmentioning
confidence: 99%
“…7 This plant has been investigated for its myriad biological effects such as antihyperglycaemic and hypolipidaemic, hepatoprotective, antioxidant activity and came out with promising results. [8][9][10] In light of above reports, it is reasonable to assume that this plant could have anticancer potential. Hence, in this study we investigated the cytotoxic potential of C. fimbriata ethanolic leaf extract against human COLO 320 cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%